Difference between students’ and parents’ demand for educational function of study tour products - Yu, Yaqi; Marzuki, Azizan (Edelweiss Applied Science and Technology, 2025)
Study tour products possess both tourism and educational attributes. Understanding consumer psychology is key to satisfaction, yet student and parent demands remain understudied despite their stakeholder importance. Therefore, this paper aims to analyze the demands and differences between students and parents for the educational functions of products based on the theory of multiple intelligences and the theory of classification of educational objectives. Based on the survey results from 815 respondents, this study classified and analyzed the differences of consumer demands based on the Kano model to determine the priority order for meeting the demands of students and parents. The results showed that there were typical differences between students and parents in terms of demand types, dependence and expectation characteristics. Students demonstrated robust affective and behavioral demands, whereas parents exhibited greater demands in the cognitive and behavioral dimensions. This disparity reveals that in the design of study tours, the experience demands of students and the educational outcome expectations of parents need to be taken into account. These findings offer practical guidance for practitioners to optimize product design and formulate differentiated marketing strategies, which is of significant practical importance for enhancing the satisfaction and market competitiveness of study tour products.